La esclavitud indígena, el caso de Colchagua - Muñoz Correa, Juan Guillermo (Revista de Historia Social y de las Mentalidades, 2011)
In the immediate aftermath of the indigenous uprising of 1598 in southern Chile, which coincided with the demographic crisis of the central and northern regions and its consequent labor depletion, the colonists sought the enslavement of the rebels. This system, which had some 16thcenturyprecedents, was legally established in 1608. Based upon a regional sample and with an emphasis on social and economic factors, this article explores some traits of the enslaved Indians and their geographic destinations after their legal manumission in 1683